Lead-acid batteries for future automobiles - Garche, Jeurgen; Karden, Eckhard 1967-; Moseley, Patrick T.; Rand, D. A. J. 1942- (David Anthony James) (Elsevier, 2017)
Lead-Acid Batteries for Future Automobiles provides an overview on the innovations that were recently introduced in automotive lead-acid batteries and other aspects of current research. Innovative concepts are presented, some of which aim to make lead-acid technology a candidate for higher levels of powertrain hybridization, namely 48-volt mild or high-volt full hybrids. Lead-acid batteries continue to dominate the market as storage devices for automotive starting and power supply systems, but are facing competition from alternative storage technologies and being challenged by new application requirements, particularly related to new electric vehicle functions and powertrain electrification.--Provided by publisher.